Integrated ocean monitoring including ozone - DAS, S. K.; CHATTERJEE, KALIPADA (MAUSAM, 1984)
The importance of integrated ocean monitoring in relation to weather over the South Asia, particularly over the Indian Ocean has been discussed by many scientists. During December to February 1981-82 and 1982-83 two scientific cruises were undertaken by the Indian scientists over the Arabian Sea, Indian Ocean and Southern Ocean and a large volume of integrated meteorological and ocean data were collected. The present paper deals with the study' and analysis of the data of sea surface temperature (SST), surface pressure, ambient temperature, wind, upper air meteorological parameters and atmospheric ozone near the sea surface, collected during the 1982.83 cruise. The findings of this paper may provide additional inputs to the scientists studying various atmospheric processes over the Indian Ocean and Southern Ocean affecting monsoon m particular and weather in general over the South Asia.